MATRIX INDEX OF INCOME VARIETIES OF INDONESIAN LABOR FORCE AND ITS APPLICATION IN INDONESA - Canon, Syarwani (Journal of Indonesian Economy and Business, 2012)
Matrix Index of Income Varieties (MIVP) is an index, which is developed from theÂ variety co efficiency and statistic Ï2 so that it will produce output totally as shown byÂ Index of Williamson/Theil, as regionally as Index of Theil, sectorally as Index of Gini.Besides, Matrix Index of Income Varieties (MIIV) is able to identify which individual/Â sector/region influence the draw of income inequalities above or below the average. InÂ application, MIIV will produce a maximal outcome if it is combined with Labor ForceÂ Productivity Index.The outcome of MIIV/MIVP in Indonesia shows that the high-income inequalities inÂ Indonesia are influenced by the contribution of regional economy, regional labor forceÂ contribution, the characteristic of regional economic sector, and regional potentials ofÂ each province.Keywords: income distribution, total, region, sector, regional sector